Global exponential stability of nonresident computer virus models - Tang, C.; Wu, Yong Hong (Pergamon, Elsevier Ltd, 2017)
© 2016 Elsevier LtdThis paper is concerned with nonresident computer virus models which are defined on the nonnegative real vector space. By using differential inequality technique, we employ a novel argument to show that the virus-free equilibrium is globally exponentially stable, and the exponential convergent rate can be unveiled. Moreover, a numerical simulation is given to demonstrate our theoretical results.